Onshore and Offshore Market of Chinese Yuan - Markiewicz, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Chinese yuan is a financial instrument of growing importance in the regional and world scale. Slow liberalization of capital flows in relation to the yuan has contributed to increase in its use in the trade and financial accounts, especially outside the home country. In the article it was formulated the hypothesis that the most important factor for the internationalization of the yuan is a dynamic development of the offshore market in the financial centre of Hong Kong. With the aim to verify the hypothesis there are analyzed: the characteristics of the offshore market in Hong Kong, the determinants and importance of the yuan exchange rate and the comparison of the onshore and offshore renminbi market. Based on data from Thomson Reuters service there are examined changes in the exchange rate of the CNY/USD and CNH/USD in 2010–2014 on the spot market, as well as a detailed analysis concerning the development of the spread between these units.